Diffusion NMR spectroscopy - Klaas Nicolay; Kees P. J. Braun; Robin A. de Graaf; Rick M. Dijkhuizen; Marijn J. Kruiskamp (2001)
Abstract MR offers unique tools for measuring molecular diffusion. This review focuses on the use of diffusion‐weighted MR spectroscopy (DW‐MRS) to non‐invasively quantitate the translational displacement of endogenous metabolites in intact mammalian tissues. Most of the metabolites that are observed by in vivo MRS are predominantly located in the intracellular compartment. DW‐MRS is of fundamental interest because it enables one to probe the in situ status of the intracellular space from the diffusion characteristics of the metabolites, while at the same time providing information on the intrinsic diffusion properties of the metabolites themselves. Alternative techniques require the introduction of exogenous probe molecules, which involves invasive procedures, and are also unable to measure molecular diffusion in and throughout intact tissues. The length scale of the process(es) probed by MR is in the micrometer range which is of the same order as the dimensions of many intracellular entities. DW‐MRS has been used to estimate the dimensions of the cellular elements that restrict intracellular metabolite diffusion in muscle and nerve tissue. In addition, it has been shown that DW‐MRS can provide novel information on the cellular response to pathophysiological changes in relation to a range of disorders, including ischemia and excitotoxicity of the brain and cancer. Copyright © 2001 John Wiley & Sons, Ltd. Abbreviations used: ADC apparent diffusion coefficient ADP adenosine diphosphate Cho choline‐containing compounds DW diffusion‐weighted 2FDG‐6P 2‐fluoro‐2‐deoxyglucose‐6‐phosphate geMQC gradient‐enhanced, multiple‐quantum coherence NAA N ‐acetylaspartate PCr phosphocreatine PFG pulsed field gradient PRESS point‐resolved spectroscopy STEAM stimulated‐echo acquisition mode tCr total creatine/phosphocreatine.